Perlindungan Hukum Pidana terhadap Anak dan Wanita Berdasarkan Undang-Undang Perlindungan Anak dan Undang-Undang Penghapusan Kekerasan dalam Rumah Tangga - Rahayu, Agil Faradina; Irawati, Arista Candra; Irhamdessetya, Hani (VISA: Journal of Vision and Ideas, 2025)
Domestic violence (DV) represents a serious violation of human rights that frequently occurs in the private sphere, with children and women being the most vulnerable groups. Although Indonesia has established a relatively comprehensive legal framework, such as Law Number 35 of 2014 on Child Protection and Law Number 23 of 2004 on the Elimination of Domestic Violence, the enforcement of criminal legal protection for victims remains suboptimal. This research aims to analyze the effectiveness of the application of criminal sanctions within these laws and to critically evaluate the gap between legal norms and actual implementation. The study employs a normative juridical method by examining statutory regulations, legal doctrines, and relevant literature. The results indicate that, although the laws provide a detailed normative basis regarding the forms of violence and corresponding criminal sanctions, there are significant challenges in practice, including weak institutional coordination, limited support infrastructure, and the persistent influence of patriarchal cultural norms. Additionally, overlapping legal provisions often create ambiguity in legal enforcement processes. Therefore, this study underscores the need for harmonization of laws and a reformulation of criminal justice policies that are more victim-centered and aligned with human rights principles. Strengthening legal protection systems through inter-institutional synergy and increasing public legal awareness are essential steps toward achieving substantial justice for victims of domestic violence, particularly women and children.